Pedagogical Translation: Nature and Benefits - Abdellah Badda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The controversy about using L1 in the EFL classroom has always been heated. Despite the overwhelming claims which call for a serious total rejection of L1 in EFL teaching, it has been admitted in the literature that L1 still finds its way to the EFL classroom practices either strategically or unintentionally. Recent research shows that the use of L1 can still be appreciated by students and teachers on the grounds that there are undeniable benefits of implementing learners’ mother language in class. In this paper, the researcher examines the possible benefits of using L1 in EFL classes. Pros of incorporating L1 are highlighted in light of which the researcher highlights the view that a controlled systematized incorporation of translation exercises can find some room in EFL teaching. However, the practical extent of implementing L1 is being questioned for there is scarce theorisation on how translation can be incorporated practically without affecting students’ need for maximum exposure to L2. The article concluded with a call for more empirical research which can narrow the gap between the stances of acceptance and a practical implementation of translation tasks in foreign language teaching.